PENGARUH KEPERCAYAAN, KEMUDAHAN, DAN RISIKO TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN PEMBAYARAN SHOPEE PAYLATER - SUCIARNI RAMADHAN; NINA KARINA KARIM; NURABIAH NURABIAH (GANEC SWARA, 2024)
This research aims to analyze the influence of trust, convenience and risk on purchasing decisions using Shopee Paylater payments. This type of research is associative research using primary data obtained through distributing questionnaires to 403 respondents who are the millennial generation and generation z in Sape District. The data analysis technique in this research was carried out using the Partial Least Square (PLS) method using SmartPLS 3.0. The results of this research show that the trust variable influences purchasing decisions using Shopee Paylater, the convenience variable influences purchasing decisions using Shopee Paylater, and the risk variable influences purchasing decisions using Shopee Paylater payments. This research supports the TPB theory in explaining the factors that influence purchasing decisions. It is hoped that the results of this research can be input for companies, especially e-commerce companies, regarding the development of their marketplace, so that in the future they can be more innovative and provide confidence and convenience to consumers, especially the millennial generation and generation z